PHYSICOCHEMICAL, PHYTOCHEMICAL AND HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY ANALYSIS OF THE ROOT BARKS OF ONOSMA ECHIOIDES - Shoaib, Ambreen; Siddiqui, Hefazat Hussain; Badruddeen, Badruddeen; Rizvi, Aleza; Dixit, Rakesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Onosma echioides (OE) L., family Boraginaceae, is most recurrently used remedial herb, which is extensively dispersed all over India. It is used as purgative, bladder obstacle, liver chaos, kidney obstruction, sciatic pain, and gout. The study was meant to carry out the physicochemical, phytochemical, and high-performance thin layer chromatography (HPTLC) analysis on root bark of OE. Methods: The physicochemical parameters were carried out as per the World Health Organization guideline. The preliminary chemical test was performed as per pharmacopeia and conventional methods. Camag HPTLC system equipped with TLC autosampler 4 applicator, TLC scanner 3 and win CATS 1.4.4. Software was used for HPTLC analysis of plant extract with standard, i.e., shikonin. The extracts were developed using toluene:ethyl acetate:formic acid (5:4:0.3) as a mobile phases using standard procedures and scanned under ultraviolet 254 nm and 366 nm. Results: OE is composed of sterols, tannins, alkaloids, flavonoids, glycoside, saponin, and carbohydrates. The plant was found to be free from adulteration and contamination. The fluorescence characteristics of leaf powder were studied both in visible light and ultraviolet light (254 nm and 365 nm) after treatment with various reagents. The TLC plate showed several spots at different Rf when viewed under 254 nm, 366 nm. The HPTLC profile showed several peaks that indicated the presence of various phytochemicals along with its active constituent, i.e., shikonin. Conclusion: The study provides referential information for the standardization of the plant. The HPTLC profile will help in authentication and standardization of the plant.